Semirelativistic Potential Modelling of Bound States: Advocating Due Rigour - Lucha Wolfgang (EPJ Web of Conferences, 2022)
The Poincaré-covariant quantum-field-theoretic description of bound states by the homogeneous Bethe–Salpeter equation usually exhibits an intrinsic complexity that can be attenuated by allowing this formalism to undergo various simplifications. The resulting approximate outcome’s reliability can be assessed by applying several rigorous constraints on the nature of the bound-state spectra; most prominent here are existence, number and location of discrete eigenvalues.